Analysis of The Differentiated Learning Implementation in Science and Social Science Learning on the Independent Curriculum at Elementary School - Harris setiawan; Nur Ngazizah; Suyoto (JIP Jurnal Ilmiah PGMI, 2025)
This study was conducted with the aim of analyzing whether the application of differentiated learning has accommodated the needs of students' learning styles and reviewing in more depth how the application of differentiated learning in science subjects in optimizing the independent curriculum. The number of informants in this study was one fourth grade teacher. And thirty students in the application of learning in class. This type of research uses a qualitative method and uses a descriptive approach. Data collection through interview methods with fourth grade teachers, observation and documentation obtained from teaching modules, LKPD, produced by students, teaching materials and other supporting documents. Data validity testing uses triangulation of techniques and sources. The data analysis technique follows the Miles and Huberman procedure which contains three techniques; data reduction in the context of this study in the form of interview results, observations, documentation and student learning questionnaire results, presentation of data from the results of the reduction is presented in the form of tables and descriptive narratives and finally drawing conclusions. The findings of the analysis show that learning styles influence the achievement and learning outcomes through a differentiated approach. By implementing the four aspects and steps of differentiated learning, learning is not only more focused but also makes it look enthusiastic, the classroom atmosphere becomes fun which is supported by adequate facilities and infrastructure and improves student learning outcomes. This study, the application of differentiated learning is an effective approach because students get learning experiences that are in accordance with their interests and learning needs so that students become more motivated and appreciate differences in learning styles and teachers become more creative and innovative even though they sometimes add lessons outside of class hours so that students get good learning grades.